2022
DOI: 10.1111/inm.13024
|View full text |Cite
|
Sign up to set email alerts
|

Communication pathways from the emergency department to community mental health services: A systematic review

Abstract: This systematic review synthesizes existing peer reviewed evidence reporting on evaluated strategies used for enhancing communication pathways for continuity of care between the emergency department and mental health community supports. Following the PRISMA guidelines and the PICO framework, this review was conducted between January and July 2021. Included articles needed to evaluate communication pathway interventions for continuity of care between the emergency department and mental health community services… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
(123 reference statements)
0
2
0
Order By: Relevance
“…The use of tools, such as mental health advance care plans, would enable people presenting to the ED to provide their wishes to clinicians and save time during the doctor/patient interview, including who to contact, information sharing permissions and privacy concerns (Lasalvia et al., 2023). Pre‐consent and/or disclosure agreements could be added to current ED and NDIS provider systems and would greatly assist with the continuity of care between the two services (McIntyre et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of tools, such as mental health advance care plans, would enable people presenting to the ED to provide their wishes to clinicians and save time during the doctor/patient interview, including who to contact, information sharing permissions and privacy concerns (Lasalvia et al., 2023). Pre‐consent and/or disclosure agreements could be added to current ED and NDIS provider systems and would greatly assist with the continuity of care between the two services (McIntyre et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…As people with PSD often have a combination of medical and mental health needs, improving practices in the ED setting that incorporate wholistic, person focussed care (Procter et al, 2022;Sacre et al, 2022), including strengths-based recovery (Hayes et al, 2018;Lorien et al, 2020) and social theory approaches (Bunbury, 2019;Shakespeare & Watson, 2001) to augment a biomedical approach, will give a foundation to improve person-centred care and quality-of-care responses. Positive communication practices between services to enable follow-up with other support services will assist with continuity of care (McIntyre et al, 2022). People with complex conditions and social support needs are seeking help from the ED despite this service not being adequate to provide care at the required level (Roennfeldt et al, 2021;Sacre et al, 2022) and without established and budgeted service integration pathways (Mavromaras et al, 2018).…”
Section: Ed Engagementmentioning
confidence: 99%
“…Working side by side and coconstructing care are widely considered essential for safety in mental healthcare to build rapport and decrease distress [31,58]. Ten, the person is better placed to ask questions, seek clarifcation, and leave the ED with coordinated planned actions, which will reduce healthcare avoidance in future [32,35,59].…”
Section: How To Make the Ed Safementioning
confidence: 99%
“…Many studies report on gaps in system communication between the ED and primary care support post an ED presentation [30,59,62,63]. Parallel to this, communication with health services and the NDIS has been highlighted as an issue systemwide [17,19,48,64].…”
Section: Connecting the Communication Silos-service Integrationmentioning
confidence: 99%
“…For every completed suicide in adolescents, there may be as many as 50 to 100 attempts� 4 Several organizations, including the WHO, state that a previous suicide attempt is the single most important risk factor for suicide� 5 Other risk factors include psychiatric disorders, family history of mood disorders, history of physical or sexual abuse, exposure to violence, and biologic factors� 4 An evidence brief by the Mental Health Commission of Canada reported that 10% to 15% of people seen in a hospital emergency department for a suicide attempt will repeat the attempt within 12 months following discharge� 6 Up to 70% of individuals who survive a suicide attempt do not attend their first outpatient appointment, so several follow-up and regular contact interventions can be implemented to help ensure the continuity of care for these individuals� 6 These active follow-up interventions include telephone calls, text messages, emails, letters or postcards, and home visits� The National Institute for Health and Care Excellence (NICE) recommends the following: "If there are ongoing safety concerns for the person after an episode of self-harm, the mental health team, GP, team who carried out the psychosocial assessment or the team responsible for their care should provide initial aftercare within 48 hours of the psychosocial assessment�" 7 Most recommendations regarding follow-up after an episode of self-harm or suicide attempt are developed using evidence generated from adults� Several systematic reviews (SRs) have been published that evaluate the effectiveness of active follow-up care; however, they also include adult populations and/or other interventions� [8][9][10][11][12]…”
Section: Context and Policy Issuesmentioning
confidence: 99%